If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-9(n-7)=12-4(n+1)
We move all terms to the left:
-9(n-7)-(12-4(n+1))=0
We multiply parentheses
-9n-(12-4(n+1))+63=0
We calculate terms in parentheses: -(12-4(n+1)), so:We get rid of parentheses
12-4(n+1)
determiningTheFunctionDomain -4(n+1)+12
We multiply parentheses
-4n-4+12
We add all the numbers together, and all the variables
-4n+8
Back to the equation:
-(-4n+8)
-9n+4n-8+63=0
We add all the numbers together, and all the variables
-5n+55=0
We move all terms containing n to the left, all other terms to the right
-5n=-55
n=-55/-5
n=+11
| 7/4n=1/4 | | d•3=-81 | | -12y=22 | | 9c-3c-5c+2c-c=14 | | 9x+70+20x=12 | | 48+1/5x=73 | | 347.50+45x=100 | | -5u=8 | | 347.50x+45=100 | | 180=78x-6x^2 | | -12+5(5r-11)=38+10r | | -7x-5=-4-29 | | 12r+4r+r-11r+3r=9 | | 3n-2(-2-7)=4(1-8n) | | N-5=2n-n | | 8v=-7−9v | | 10x-17=87 | | 26+10x7=36+8 | | 347.50x+100=45 | | 26+10x=36+8 | | -7+3k=8 | | -20=-9n | | 2(p+1)=184 | | 45x=100=347.50 | | (2-7x)=(8x+3)2 | | 11n-1+5n=65n-36 | | 3a-a+10-5=25+2a | | (5x+7)+82=180 | | 16=5v | | 1-3r=-4r-9+7 | | 19j+4j+j-22j=8 | | 2j+9=5j+ |